Menumbuhkan Literasi Lingkungan dan Self-Confidence Melalui Model Pembelajaran Contextual Teaching and Learning Berorientasi Nilai Lingkungan dalam Pembelajaran Biologi - Bayu Anshor Mursalin; Edo Wijaya; Ambar Indriyani; Tisya Selviani Ariyamti (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Environmental literacy and student character development are essential to be improved, given the increase in national waste generation to 31.32 million tons by 2024 and the low self-confidence of children, according to the International Women's Day 2022 survey. In addition, preliminary research shows that students have low self-confidence and environmental literacy. Therefore, this study aims to evaluate how effective the environmental values-oriented contextual Teaching and Learning (CTL) model is in increasing students' knowledge and confidence about biology in secondary school. This research method uses a quasi-experimental approach with a non-equivalent control group design. The experimental class obtained learning using the CTL model that integrated environmental values (ecocentric), while the control class received conventional learning. Data was obtained through environmental literacy tests, validated self-confidence questionnaires, and observation sheets. The reliability of all devices is very high (Cronbach's alpha, α > 0.80). The results of independent t-test samples, correlation analysis, and regression analysis showed that the experimental group obtained significantly higher post-test scores and N-gain values than the control group, both for environmental literacy (N-gain 0.80; high category) and confidence (N-gain 0.74; high category). Regression analysis showed that the environmental value-oriented CTL model contributed 70.3% to the increase. The results of this study show that contextual learning that integrates environmental values not only improves students' conceptual understanding but also enhances their affective aspects. Therefore, the environmental value-oriented CTL model can be an effective pedagogical strategy to help curriculum reform and teacher professional development in increasing environmental awareness and character formation of students.